Extracorporeal Membrane Oxygenation in the Management of Diffuse Alveolar Hemorrhage. Issue 2 (March 2015) - Abrams, Darryl; Agerstrand, Cara L.; Biscotti, Mauer; Burkart, Kristin M.; Bacchetta, Matthew; Brodie, Daniel
Abstract : Extracorporeal membrane oxygenation (ECMO) may be used to support patients with severe hypoxemic respiratory failure refractory to conventional mechanical ventilation. However, because systemic anticoagulation is generally required to maintain circuit patency, severe bleeding is often seen as a contraindication to ECMO. We describe our center's experience with four patients who received ECMO for refractory hypoxemic respiratory failure due to diffuse alveolar hemorrhage (DAH), a condition for which anticoagulation is typically contraindicated, and provide a review of the literature. The mean age was 35.8 ± 16.4 years. The mean pre-ECMO PaO2 to FIO2 ratio was 52.3 ± 9.4 mm Hg. All patients were treated with continuous infusions of heparin with a goal-activated partial thromboplastin time between 40 and 60 seconds (mean, 47.4 ± 11.6 seconds). All four subjects (100%) survived to decannulation, and three subjects (75%) survived to discharge. The results from this case series, along with previously published data, suggest that ECMO is a reasonable management option for patients with DAH-associated severe, refractory hypoxemic respiratory failure. This is especially true in the era of modern ECMO technology where lower levels of anticoagulation are able to maintain circuit patency while minimizing bleeding risk.